The effect community empowerment of adolescent to increase knowledge and attitude of young age marriage - Dwiana Estiwidani; Tri Maryani (Jurnal Kesehatan Ibu dan Anak, 2018)
Young age marriage was one of the most international issues and was mostly done in developing countries including Indonesia. The strongest factor was poor adolescent perception. Improvement of knowledge and attitude of adolescent reproductive health could be done with preventive health promotion. Adolescent tend to against from their teachers or parents and prefer to mingle or trust their peers. Gunungkidul Regency was the region with the highest incidence of young age marriage in the province of Yogyakarta in 2015. The research objective was to know the influence of community empowerment of adolescent to increase knowledge and attitude of young age marriage. Research method of experiment with pretest-postest with control group design. Location was in Wonosari District. The number of samples was 50 respondents selected bytwo stagesimple cluster sampling, both in the experimental group with the counseling by the adolescents who had been trained or controlled by the extension by the midwife of the PHC. The data collection instrument was questionnaire. Bivariable analysis using paired sample t-test and independent sample t-test, Wilcoxon and Mann-Whitney. Multivariable analyzed with logistic regression. The result of knowledge and attitude before the intervention given to both groups in sufficient category. The average after intervention in either category. There is an increase in the average knowledge and attitude on evaluation I and II in each group (p value: <0,05). There was no difference in the average improvement of evaluation knowledge I, there was a difference of average improvement of evaluation knowledge II, and there was a difference of the average increase of evaluation attitude I and II between the two groups. There was influence of empowering adolescent to increase knowledge and attitude of young age marriage.